2020
DOI: 10.1039/d0sc04597g
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective addition/annulation of ferrocenyl thioamides with 1,3-diynes via a sulfur-transfer rearrangement to construct extended π-conjugated ferrocenes with luminescent properties

Abstract: Regioselective addition/annulation of ferrocenyl thioamides with 1,3-diynes has been developed to construct extended π-conjugated ferrocenes with luminescent properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The authors conducted various mechanistic studies and revealed that the thiocarbonyl group undergoes addition and intramolecular sulfur-transfer rearrangement on 1,3-diyne to furnishes the ThienylFc moieties (Scheme 46). [39] The possible catalytic cycle shown in Scheme 47. The mechanism initiated with formation of active catalyst-A by ligand exchange, which subsequently coordinate and active the CÀ H activation of ferrocenyl thioamides to deliver the intermediate-B.…”
Section: Oxygen or Sulfur Bearing Heterocyclesmentioning
confidence: 99%
“…The authors conducted various mechanistic studies and revealed that the thiocarbonyl group undergoes addition and intramolecular sulfur-transfer rearrangement on 1,3-diyne to furnishes the ThienylFc moieties (Scheme 46). [39] The possible catalytic cycle shown in Scheme 47. The mechanism initiated with formation of active catalyst-A by ligand exchange, which subsequently coordinate and active the CÀ H activation of ferrocenyl thioamides to deliver the intermediate-B.…”
Section: Oxygen or Sulfur Bearing Heterocyclesmentioning
confidence: 99%
“…In 2020, You's group has reported a regioselective addition/ annulation sequence of ferrocenyl thioamides 162 with alkynes 163 to construct thienylferrocene (ThienylFc) structures 164, which includes rhodium-catalyzed CÀ H activation, an unusual C2-selective addition of 1,3-diyne and an unexpected intramolecular sulfur transfer rearrangement (Scheme 41A). [91] 1,4-Diphenyl-1,3-butadiynes with electron-donating and electronwithdrawing substituents in the para-or meta position of the phenyl ring afford the desired products. In this protocol, thioamide serves not only as a directing group to activate the ortho-CÀ H bond of ferrocene but also as a sulfur source to provide the indispensable heteroatom for the formation of the thiophene ring.…”
Section: Rh Catalysismentioning
confidence: 99%
“…39 A worthwhile endeavor would thus be to develop a double annulation method linked to the construction of S-enabled heterocycles through CH activation of thioamides. [40][41][42][43] Envisaging a complete coordination switch-over from 'N' to 'S' to TM would result in a metalated isothiochromenimine species B-II from mono-annulation of thioamide's S-moiety with an alkyne (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%